1986
DOI: 10.1080/09553008614550641
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock (45°C) Results in an Increase of Nuclear Matrix Protein Mass in HeLa Cells

Abstract: The nuclear matrix from HeLa cells heated at 45 degrees C was isolated to determine the effect of thermal shock on its composition and structure. The matrix from unheated cells contained about 10 per cent of total cell protein and was observed to be spherical particle with a diameter ranging from 3 to 5 microns with the major constituent polypeptides having molecular weights of 45, 47, 55, 57, 59 and 65 kilodaltons. The nuclear-matrix protein mass increased linearly with increasing exposure time at 45 degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 27 publications
2
22
0
1
Order By: Relevance
“…Thermal denaturation of (nuclear) proteins resulting in aggregation of usually soluble nuclear proteins (see Kampinga, 1993, for review) with the (insoluble) nuclear matrix was found to correlate with the inhibitory effect of heat on m-AMSA toxicity (Kampinga et al, 1989a). This aggregation also was found to be related to altered DNA-matrix attachment interactions (Warters et al, 1986;Sakkers et al, submitted). In HeLa S3 cells, the initial aggregation is the same in thermotolerant cells as in non-tolerant cells (Kampinga et al, 1987(Kampinga et al, , 1989c, consistent with the observation that thermal protection against drug toxicity and break formation is about the same in thermotolerant and non-tolerant cells (Figures 4 and 5).…”
Section: Resultsmentioning
confidence: 97%
“…Thermal denaturation of (nuclear) proteins resulting in aggregation of usually soluble nuclear proteins (see Kampinga, 1993, for review) with the (insoluble) nuclear matrix was found to correlate with the inhibitory effect of heat on m-AMSA toxicity (Kampinga et al, 1989a). This aggregation also was found to be related to altered DNA-matrix attachment interactions (Warters et al, 1986;Sakkers et al, submitted). In HeLa S3 cells, the initial aggregation is the same in thermotolerant cells as in non-tolerant cells (Kampinga et al, 1987(Kampinga et al, , 1989c, consistent with the observation that thermal protection against drug toxicity and break formation is about the same in thermotolerant and non-tolerant cells (Figures 4 and 5).…”
Section: Resultsmentioning
confidence: 97%
“…It is conceivable that the insolubilization and translocation of HSP27 during heat shock simply reflect the protein denaturing effect of heat. A large number of other proteins are similarly insolubilized and associate with nuclear structures during heat shock (13,23,24,33,45,54).…”
Section: Discussionmentioning
confidence: 99%
“…Heat-shocked cells present strong alterations of chromatin structures, exhibiting a markedly condensed chromatin (Iliakis and Pantelias 1989;Warters et al 1986), a weaker sensitivity to DNaseI (Pekkala et al 1984) as well as a weaker sensitivity to diffusible mitotic factors (Iliakis and Pantelias 1989). One of the described molecular effects of heat shock on chromatin components is increased histone H1 phosphorylation in vivo (Glover et al 1981).…”
mentioning
confidence: 99%